Structurally coordinated aggregation induced emission ionic supramolecular cages. (March 2023) - Han, Xin; Hu, Weinan; Miao, Lingling; Hao, Xin-Qi; Shi, Linlin; Song, Mao-Ping
Abstract: Over the course of the last 20 years, the research of aggregation-induced emission (AIE) has made great strides in mechanistic understanding, structure-property relationships, and high-tech applications. Aggregation-induced emission luminogens (AIEgens) have emerged as a novel type of advanced material with excellent performance in various fields including fluorescent imaging, bio-probes, chemical sensors, photonic drugs, and optoelectronics. Stimuli-responsive photoluminescence materials also attracted extensive research interest for applications in information security and encryption. Herein, two discrete tertrahedral metallo-supramolecular cages were designed and constructed using truxenepended base ligands. Owing to the completely different characteristics of conjugated aromatic oligo(phenylenevinylene) (OPV ) pyridinium skeleton and alkyl group linked aliphatic quaternary ammonium moiety suspended by the truxene skeleton, the resulting supramolecular cages were confirmed to exhibit a significant aggregation-induced emission (AIE) accompanied by an interesting variable fluorescent behavior. In particular, the anticounterfeiting performance of the cages was investigated, and indicated that the cages C1 and C2 could be used for information encryption.